Quantitative determination of main groups of substances in granules on the basis of medicinal vegetable raw material for treating gastrointestinal diseases - Spiridonov, S; Kotov, A (Annals of Mechnikov’s Institute, 2020)
In the last time a significant increasing of gastrointestinal tract diseases has been observed. The poor quality and irrational feeding, environmental pollution, psychological and other factors is the causes of this. Very often the gastrointestinal tract has a multifactorial pathological effects, also affecting the hepatosphere organs and urogenital system. Also a great importance have accompanying disorders of the central nervous system. Thus we must to require a comprehensive approach to the creation of drugs for use in gastroenterology, the assortment range of which should be expanded. Advantageous position in this case takes a phytotherapy using drugs based on medicinal plant raw material, which acting on the main areas of the pathological process. For this purpose the scientists from the National University of Pharmacy (Kharkov, Ukraine) was created a complex herbal drug in the form of granules under the code name "Poligerbagastrin", includes the following types of medicinal plant raw material powders: helichrysum arenarium flowers, corn stigmas, horsetail grass, knotweed grass, horse chestnut seeds, licorice roots and wheat bran. Materials and methods. To determine the quantity of biologically active substances the method of spectrophotometry in the visible and UV spectral region was used. This method is well studied and available, equipped with high-precision hardware. He also described in the Ukrainian normative documents and contained in the world’s leading pharmacopoeias. For determination was used the unifieds methods, which shown in pharmacopoeia monographs and other reference literature. Determination was carried out with a spectrophotometer HP 8543 UV-VIZ of «Hewlett Packard» company, USA. Results and discussion. For the quantitative determination of flavonoids was used a methodology, which based on the complexation reaction of isolated by acid hydrolysis and extraction with ethylacetate hydrolysis products with aluminum chloride in methanol - ethyl acetate - acetic acid environment and calculation of flavonoid content as hyperoside recalculating. For the quantitative determination of polyphenols was used the methods of State Pharmacopoeia of Ukraine "Determination of tannins in herbal drugs" or European Pharmacopoeia «Determination of tannins in herbal drugs». The method is based on the color reaction of polyphenolic substances, which including in the plant raw material, with phosphomolybdic-tungsten reagent and measuring the optical density of the resulting solution at the wavelength of 760 nm. The content of total polyphenols in the drug was determined as pyrogallol recalculating. Conclusions. 1. The determination of quantitative content of biologically active substances in granules based on medicinal plant raw material for the treatment of gastrointestinal tract diseases is carried out. 2. In the studied sample of granules contents of flavonoids, calculated as hyperoside, which equal to 0.43% and the polyphenols, calculated as pyrogallol, which equal to 0.44% has been established. 3. The data obtained can be used to develop the normative and technical documentation.